PEDAGOGICAL NEED FOR THE FORMATION OF MODERN PROFESSIONAL QUALITIES THROUGH VIRTUAL TECHNOLOGIES IN TEACHERS OF FUTURE TECHNOLOGICAL EDUCATION IN HIGHER EDUCATIONAL INSTITUTIONS - B.B.Umrzaqov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article describes the pedagogical need for the formation of modern professional qualities through virtual technologies in future teachers of technological education in higher educational institutions.